Strategies for Implementing Artificial Intelligence in Human Resource Management - Suprayitno Suprayitno (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to identify and analyze strategies for implementing Artificial Intelligence (AI) in Human Resource Management (HRM) through a comprehensive literature review. The research explores AI applications in key HR functions such as recruitment, onboarding, performance management, and employee development. It also evaluates the challenges faced during AI adoption, including ethical concerns, algorithmic bias, and organizational resistance. Additionally, the study highlights critical success factors like leadership support, digital competency development, and organizational culture adaptation. The findings provide valuable insights for organizations seeking to integrate AI ethically and effectively to enhance HR processes and overall organizational performance.